Satisfaction analysis of atrium day lighting in Jordanian residential building - Jaradat, Haitham
Globally, daylight is an important issue in the modem architecture. Since, it affects the functional arrangement of spaces, occupant comfort, structure, and energy use in the buildings. Locally, in Jordan, there is a lack of studies that deal with architectural and interior design efforts to address the indoor daylight quality in houses. Also, Atrium houses are not wideIy spread in Jordan. The study aimed to; measure the satisfaction levels' of atrium roof residents with daylight at Jordan in terms of interior design suitability, thermal comfort, and interior visual comfort. The research methodologies are quantitative and cross-sectional ones'. The study conducted in Amman, Jordan. A sample of 35 respondents filled the self-administration questionnaire properly. The questionnaire had been developed based on previous studies, and its validity and reliability were done. The content validity had been ensured, since the questionnaire scales and subscales items' were quoted from previous studies and the pilot study approach had been adopted to measure the questionnaire items reliabilities. Of them, 40.3% females, 59.7% male The age of respondents' ranges from less than 25 years old and to above 50 years old. Ridge Roof type has the largest share percentage in total roof types included in the research 68.2%. The collected data were coded and SPSS version 23 used to analyse them. The study concluded that, Jordanians were satisfied regarding the daylight in their atrium roofs in terms of interior design suitability, thermal comfort, and interior visual comfort. Also, th re was a statistically significant difference among respondents regarding the "interior design suitability" in the favour of males. In regarding to the interior design suitability, the youngest respondents', whom age group is less than 25 years old, had the lowest satisfaction level, while the second age group, whom are only five years older than youngest respondents, had the highest satisfaction level. In addition, respondents have the same satisfaction levels toward the thermal comfort subscale. However, respondents' satisfaction does not follow the same pattern as the interior design subscale and thermal comfort ubscale perceptions, since the third age group, who ages are between 31-35 years old, had the lowest satisfaction level, and the second age group, whom ages are between 26-30 years old, had the highest satisfaction level. In addition, roof type did not influence on the Jordanian satisfaction levels of daylight in Atriums. The research findings suggest that Atrium Day Lighting in Jordanian residential building is crucial to be analysed and it is also significantly dependent on the identified factors; the interior design, thermal comfort as well as the vision comfort. All of these factors help the related residential sites constructors to have an insight about the factors that need to be focused upon while designing or manufacturing the products.